Extracapsular versus intracapsular tonsillectomy: Outcomes in children with a focus on developmental delay. (January 2022) - Mukerji, Shraddha S.; Rath, Smruti; Zhang, Wynne Q.; Zhu, Huirong; Anand, Grace S.; Jones, John K.; Chelius, Daniel C.; Musso, Mary F.; Bedwell, Joshua R.
Abstract: Introduction: Outcomes following intracapsular tonsillectomy (IT) have not been well established in children with developmental delays. The objective of this study was to compare outcomes and complications between intracapsular and extracapsular tonsillectomy (TT) in pediatric patients with developmental delay (DD) in comparison to non-developmentally delayed children. Methods: This is a retrospective study of pediatric patients with DD undergoing tonsillectomy between 2016 and 2019 at a tertiary care hospital. This group included patients with Down Syndrome, Autism Spectrum Disorder, other genetic syndromes, and patients with a diagnosis of global developmental delay. Outcomes and complications were analyzed for IT and TT. Results: 2267 charts were reviewed, and 320 patients were identified with DD. Of those, 72 patients underwent IT and 248 underwent TT. In the DD cohort, the IT group had a shorter length of stay (0.97 vs 1.7 days, p < .0001) and was less likely to receive post-operative narcotic medication (2.8% vs 35%, p < .0001) and corticosteroids (9.7% vs 64%, p < .0001) during their hospital stay. Reductions in emergency room (ER) visits (5.6% vs 10%, p = .21) and post-op bleeding (PTH) (1.4% vs 4.8%, p = .31) for IT vs TT were not statistically significant in the DD group. In the NDD group, fewer patients undergoing IT returned to the ER (11% vs 2.3%, p < .0001) or had PTH (4.8% vs 0.25%, p, 0.0001) as compared to those children undergoing TT. There was no difference between parental report of symptom improvement between the groups (39% vs 33%, p = .39). Analysis of 180 patients with preoperative and postoperative sleep study data revealed post-op Apnea Hypopnea Index (AHI) improved with both techniques (74% TT vs 79% IT, p = .7). There were no differences noted for persistent obstructive sleep apnea (OSA) among the two techniques for both study groups (p = .63). Conclusion: Children with DD undergoing IT have reduced length of stay and reduced inpatient administration of post-operative opioids and steroids. IT has comparable efficacy to TT in treating symptoms of pediatric sleep apnea with a better safety profile. Overall, children undergoing IT return to the operating room less frequently than those undergoing TT. Longer follow-up studies will be needed to evaluate rate of tonsil regrowth, risk of revision surgery and persistence of OSA in these patients. Highlights: Developmental delays (DD) increase risk of complications after tonsillectomy. Outcomes following intracapsular tonsillectomy have not been well established. In the DD cohort, intracapsular tonsillectomy is associated with a reduced length of stay. In the DD cohort, intracapsular tonsillectomy is associated with decreased post-op steroids/narcotics.